Genialidade quilombola: os ramais de resistência no Maranhão - Oliveira, Ana Paula Silva (Universidade Federal de São Carlos, 2025)
In this ethnographic research I seek to understand, from a decolonial approach, the strategies of resistance and struggle of the quilombola community Ramal de Quindiua, in the face of the construction of the Ponte Antônio Jorge Dino complex and the MA-211 road, located in the municipality of Bequimão, Baixada Maranhense region. Such strategies will be proven based on multi-sited ethnography, which made it possible to construct analyzes at different times to see the impacts of the enterprise over the four years of carrying out this research (Marcus, 1994). Throughout the research, the “Ramais de Resistências” that connect throughout all the quilombola territories in the municipality of Bequimão and that have been strengthened by the political articulation of the Quilombola Movement of Bequimão (MOQBEQ) (Sousa, 2018), were a catalyst for analyzing the quilombola solidarity that was presented during the fieldwork. Adding to the fight for the definitive title of quilombola territories in the state of Maranhão, the quilombola territory of Ramal de Quindiua, the empirical field of this doctoral research, I use the countercolonial theories of Antônio Bispo dos Santos (2023) and Beatriz Nascimento (1985), to discuss the concepts of “confluences” and “body-territory” in the search to reflect and understand the realities lived within the territory-body. Based on the history, ways of life and knowledge of this community, I analyze how the notion of good living was constructed within the quilombola territory Ramal de Quindiua through the concept of “quilombola genius”. This notion helps us understand how ancestral resistance strategies of quilombola communities have ensured their existence since the Brazilian slavery period. If the ancestral struggle was guided by the search for places to live in freedom, today it is updated by the struggle to exist as subjects of rights in their territories in the face of the effects of state enterprises that make quilombola communities vulnerable. This is the case with the construction of the bridge over the Pericumã river and the paving of the MA-211 road. The way in which the Antônio Jorge Dino bridge (also known as Central/Bequimão) and the MA-211 were built highlights the environmental racism perpetrated by the State itself, since no public consultation was carried out before starting the work within the quilombola territory Ramal de Quindiua.
Quilombola geniality: the resistance branches in Maranhão
Keywords: Genialidade Quilombola.; Ramais de Resistência.; Comunidades Quilombolas do Maranhão.; Aquilombamento.; Antropologia Decolonial.; Quilombola Geniality.; Resistance Branches.; Quilombola Communities in Maranhão; Aquilombament; Decolonial Anthropology; CIENCIAS HUMANAS::ANTROPOLOGIA; 4. Educação de Qualidade